Perlindungan Hukum bagi Pencipta terhadap Buku Bajakan yang Dijual Melalui Media Online - Anggia Maharani Putri; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2022)
Indonesia as a legal state provides protection to the entire community, one of which is by providing legal protection for books as one of the copyrights. Book copyrights experience the most violations such as piracy. Many pirated books are traded through online media. The rise of pirated book sales activities through online media is important to raise this phenomenon into a study. This research aims to discuss legal protection for creators and examine the legal consequences of selling pirated books through online media. In this study using a normative legal research system with a library approach and legislation regarding copyright is needed in this research. Primary Legal Materials are the main legal materials in research obtained from legislation. The secondary legal materials contained in this study are in the form of literature books. Tertiary Legal Materials, namely supporting legal materials such as general dictionaries, legal dictionaries and encyclopaedias. The data collection technique using the method of quoting, summarizing. The result of this research shows that the protection given to the author against book piracy is to protect the moral rights and economic rights of the author so that only the author can get economic benefits from the work, not other parties. The legal consequences of selling pirated books are fines and imprisonment. It is hoped that the government can act more decisively in eradicating book piracy and the public can appreciate a creation more so that cases of book piracy in Indonesia can decrease